Praktik Tata Kelola Badan Usaha Milik Nagari Sato Sakaki di Nagari Taram, Kabupaten Lima Puluh Kota - Silsabila, Silsabila; Fauzi, Nurul; Rosita, Irda (Universitas Batanghari Jambi, 2024)
This research aims to examine in depth and interpret the governance practices of the Sato Sakaki Nagari-Owned Enterprise (BUMNag) in Nagari Taram. The research paradigm used is interpretive qualitative. The research method is a case study. Data collection techniques using in-depth interviews, observation, and document study. Data analysis techniques use the Miles & Huberman model: data reduction, display, and verification. The research results show that implementing the principle of transparency is carried out by disclosing information at the Nagari deliberations with financial reporting. The implementation of the principle of accountability is carried out with accountability by applicable regulations, which is carried out once every six months to the Nagari Taram Government and once a year through the Nagari deliberation. Implementation of the principle of responsibility is carried out by trying to sell LPG gas cheaper than in regular shops, providing pertashops, and not building businesses that are the same as those run by the community. The principle of independence is proven by the absence of intervention from other parties in the management of BUMNag only if applicable regulations do not implement the work division system. Implementing the fairness principle involves interested parties in decision-making, and various parties can provide constructive input.